If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -9 + 7x = -7 Reorder the terms: -9 + -5x + 7x = -7 Combine like terms: -5x + 7x = 2x -9 + 2x = -7 Solving -9 + 2x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2x = -7 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = -7 + 9 2x = -7 + 9 Combine like terms: -7 + 9 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 2x=14/3 | | 9(3+2l)-9l=-8+13l | | w-4.2=19.3 | | 8y^2(2y^2-6y+4)= | | Xy=20 | | -10-5n^2=326 | | w-12=25 | | 4x-16x+28=2 | | u-56=33 | | X=-35+-12x | | 4+6x=46 | | b+a=14 | | (1/2)^2 | | 2x^2(5x+2)= | | 6x(5-x)= | | 2x^2+2x-10=x^2-11x+20 | | X+12x+42=7 | | 4+5lnx=1 | | -21/2+15/8(x+32)+6/8 | | 7a-8b=8 | | z^2-6z+625=0 | | 7-4x=51 | | 57815(373)-73736272727(334)= | | x/x^-7 | | -6+x=8 | | 7x(9-x)= | | 7x(8-x)= | | -21/2=-5/8(x+32)+6/8 | | 2x/4=9/5 | | a+6-9=30 | | -15=-i/6-21 | | -9=-h/2-1 |